The Power of the Last Word in Legislative Policy Making - Bernheim, B. Douglas; Rangel, Antonio; Rayo, Luis (Econometrica, 2006)
We examine legislative policy making in institutions with two empirically relevant features: agenda setting occurs in real time and the default policy evolves. We demonstrate that these institutions select Condorcet winners when they exist, provided a sufficient number of individuals have opportunities to make proposals. In policy spaces with either pork barrel or pure redistributional politics (where a Condorcet winner does not exist), the last proposer is effectively a dictator or near-dictator under relatively weak conditions. Copyright The Econometric Society 2006.